The returns to education: A review of the empirical macro-economic literature - Barbara Sianesi; John Van Reenen (Institute for Fiscal Studies (IFS), 2002)
The idea of positive educational externalities is that the benefits of individually acquired education may not be restricted to the individual but might spill over to others as well, accruing at higher aggregation levels, in particular at the macro-economic one. We offer an extensive summary and a critical discussion of the empirical literature on the impact of human capital on macro- economic performance, with a particular focus on UK policy. Key findings include: (1) Taking the studies as a whole, there is compelling evidence that human capital increases productivity. Although there is an important theoretical distinction between the augmented neo-classical approach and the new growth theories, the empirical literature is still largely divided on whether the stock of education affects the long-run level or growth rate of the economy. A one-year increase in average education is found to raise the level of output per capita by between 3 and 6 percent according to augmented neo-classical specifications, while it would lead to an over 1 percentage point faster growth according to estimates from the new-growth theories. (2) Over the short-run planning horizon (4 years) the empirical estimates of the change in GDP for a given increase in the human capital stock are of similar orders of magnitude in the two approaches. (3) The impact of increases at different levels of edu-cation appear to depend on the level of a country's development, with tertiary/higher education being the most important for growth in OECD countries. (4) Education is found to yield additional indirect benefits to growth (in par-ticular, by stimulating physical capital investments and technological development and adoption). More preliminary evidence seems to indicate that type, quality and efficiency of education all matter for growth. The most pressing methodological problems are the measurement of human capital; systematic differences in the coefficient of education across countries (in particular between developing and developed countries) and reverse causality. We also make recommendations for future research priorities.
Keywords: C5; I2; O4; 330; Education; productivity; public policy; Bildungsertrag; Neue Wachstumstheorie; Makroökonomik; Theorie